The use of Prater’s Model: concrete solutions for Indonesian, Asian arts or others local content? - Iwan Zahar; Pindi Setiawan; Julius Andi Nugroho (2011)
Most of art lecturers were familiar with Feldman’s art criticism model because its simplicity which only four phases; describe, analyze, interpret, and judge. Prater (2002) proposed six steps to analyze the art work; prepare to critique, examine literal qualities, examine functional qualities, examine the formal qualities, examine the expressive qualities, determine the rele-vant theories. In order to know the use of Prater’s art criticism model, we investigated 140 students from Visual Communication Design, fifth semester, Tarumanegara University. The research used many Indonesian famous art paintings that vary from old master such as Af-fandi, Dullah, Basuki Abdullah, I Gusti Nyoman Lempad to recent artist such as Heri Dono, Djoko Pekik, etc. This research investigated students’ responses to interpret many Indonesian Art Paintings and other Asian’s work. We made a format out of Prater’s art criticism model; hence, the format helped the lecturer during delivery materials, student assignments, feed backs and evaluation. By using Prater’s criticism model, students chose and evaluated four paintings from one of the Indonesian best painters. The students had no difficulty in-terpreting Affandi, Basuki Abdullah and other Indonesian artists who used western painting techniques, western theories, and western criterias. In contrast, they found difficulty interpreting I Gusti Nyoman Lempad’s and some traditional artists’s work, who did not use western painting techniques, especially perspective drawing technique. I proposed to modify Prater’s art criticism model and integrate Space- Time- Plane Systems drawings into Prater’s art criticism model. According to Tabrani, P (2005), Space-Time-Plane systems drawing was the technique, which were used by prehistoric-primitive-traditional-children, and some modern masters such as Picasso, Paul Klee, Affandi, I Gusti Nyoman Lempad, etc.